The online defamation law in Malaysia and Indonesia: a comparative analysis - Siraj, Zaky (Ahmad Ibrahim Kulliyyah of Law, International Islamic University Malaysia, 2012)
Defamation law exists to balance two interests, the rights of freedom of expression and the rights of reputation. It aims to ensure the protection of the person's reputation from being attack or harm by another person. However, with the advent of the internet, the problem on defamation becomes more complicated. The nature of the internet that is easy to access and could reach millions people all over the world, make defamation through this media is more harm to the person's reputation. The present thesis thus compares the law of online defamation in Malaysia and Indonesia on some point; the relevant law of Malaysia and Indonesia relating to cyber defamation; the elements of online defamation; the liability of ISP; the defences and remedies that available under Malaysian and Indonesian law of defamation. This thesis also analyses the basic concept of defamation from Islamic perspective. The methodology of this study is a qualitative and doctrinal research using both analytical and comparative approaches. The primary sources are taken from Malaysian and Indonesian statutes and decided cases. This study also employs unstructured interview with several correspondences who are experts on the issue at hand in order to enrich the analyses on this study. This study discovers that the civil law of defamation in Malaysia is seems well-established while the criminal defamation is almost unknown. While defamation under Indonesian law of defamation is considered as a crime. This situation becomes a common issue that criminal defamation in Indonesia may limit the rights of freedom of expression and democracy. Furthermore, the Islamic law of defamation is more comprehensive and contains solutions to many problems in all circumstances. This research is concluded with a suggestion that there is a clear need for Indonesia to have well-defined provisions regarding civil defamation and criminal defamation. It is perhaps desirable that provisions on criminal defamation to be reconsidered or perhaps should be eliminated from the proposed new defamation law. On the other hand, although Malaysia has already well-established civil defamation law which in line with the principle of freedom of expression, it is better to absorb the principle of Islamic law of defamation. Because the Islamic law of defamation contains the provisions relating to all the problems of individual, communities and states as well.